AgNPs Argovit™ Modulates Cyclophosphamide-Induced Genotoxicity on Peripheral Blood Erythrocytes In Vivo; Nanomaterials; Vol. 11, iss. 8 - Castaneda-Yslas I. Ya. Idalia Yazmin; Torres-Bugarin O. Olivia; Garcia-Ramos J. C. Juan Carlos; Toledano-Magana Ya. Yanis; Radilla-Chavez P. Patricia; Bogdanchikova N. E. Nina Evgenjevna; Pestryakov A. N. Aleksey Nikolaevich; Ruiz-Ruiz B. Balam; Arellano-Garcia M. E. Maria Evarista (2021, 2021)
Title screen